Pengaruh Harga Terhadap Keputusan Pembelian Di Minimarket Tomika 7 - sudarsono; Anna Probowati; Dewi Shanti Nugrahani (STIE Rajawali Purworejo, 2025)
This research aims to analyze the influence of price on purchasing decisions at the Tomika 7 minimarket. Price is an important factor in influencing consumer behavior, especially in the context of fiercely competitive minimarkets. The research method used is a quantitative method with a survey approach. Data was collected through a questionnaire distributed to 100 respondents who were Tomika 7 minimarket customers. The research results showed that price had a significant influence on purchasing decisions. Factors such as affordability, suitability of price to product quality, and promotions or discounts are the main elements that influence customer perceptions of price. Data analysis using linear regression shows that the price variable contributes 65% to purchasing decisions, while the rest is influenced by other factors such as location, service and product variety. Thus, Tomika 7 minimarkets are advised to continue to maintain a competitive pricing strategy and provide added value through discounts or customer loyalty programs to improve consumer purchasing decisions.